Intervenções de enfermagem para a prevenção de quedas em pacientes no perioperatório - Chaves, Olga Benário Batista de Melo (2019)
Introduction: The surgical patient is included in the group of potential risk for falls due to the effects of anesthetic drugs, prolonged fasting and impaired mobility. Nursing has a fundamental and guiding role in the prevention of falls, and the Nursing Process (PE) is an ally in the implementation of preventive and effective interventions. Objective: To analyze the applicability of nursing interventions for the prevention of falls in perioperative patients. Method: This is a methodological research, developed in two stages: cross-mapping with Nursing Interventions Classification (NIC) and validation of content by 13 specialist nurses applying the Concordance Index (CI) ≥ 0.80. The research was approved by the Ethics Committee of the Health Sciences Center (CCBS) / UFPB under opinion of nº 2.559.757 e CAAE: 85295918.0.0000.5188. Results: The 214 care found in the literature were mapped with 84 activities and 26 NIC interventions. The NIC intervention that presented the highest correspondence with the literature was Prevention against Fall, which had 70 activities mapped, followed by interventions Risk Identification and Supervision, with 35 and 19 activities, respectively. Of the 26 validated interventions, 19 were considered suggested with a CI ≥ 0.80 and 07 considered additional options whit 0.65 ≤ CI ≥ 0.77, being Hypoglycemia Control, Sedation Control and Physical Containment the highest indexes. Conclusion: All the proposed interventions were validated and are therefore amenable to implementation in the prevention of hospital falls during the perioperative period.